Third demographic transition and demographic dividend: An application based on panel data analysis - González, Alejandro López; González-González, María Jesús (Bulletin of Geography. Socio-economic Series, 2018)
The third demographic transition, barely mentioned by some authors and implicit for others, refers to changes in the demographic structures of the most developed countries promoted by the most recent migratory flows, with repercussions in aspects such as age structure or the composition of the labour market. The concept of the third demographic transition revolves around the increasing presence of foreigners, many of whom take up jobs that nationals reject, as well as other more skilled posts. Using the panel data methodology, we try to explain the third demographic dividend whose impact can be seen in the labour market. The results enable us to conclude that the foreign worker differential puts downward pressure on salaries, which affects other groups. If workers are available and policies are constructive, this leads to positive results and social wealth.